2011
DOI: 10.3133/sir20115012
|View full text |Cite
|
Sign up to set email alerts
|

Gas and isotope chemistry of thermal features in Yellowstone National Park, Wyoming

Abstract: 5012_appendix1.pdf). Appendix 2. Google Earth KML file linked to sample locations (attached file;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(77 citation statements)
references
References 52 publications
(37 reference statements)
6
70
0
Order By: Relevance
“…The very negative values of the stable isotopes of water (dD& from À147 to À166 and d 18 O& from À13.5 to À20.7) testify to the main meteoric origin of the water itself, confirming previous investigations (Craig et al, 1956;Bergfeld et al, 2011). Carbon isotopic composition of Yellowstone fumarolic CO 2 , expressed in d 13 C& vs. VPDB notation, varies from À4.2& to À1.7&, suggesting that more than one source may be involved in defining the 13 C. In accordance with previous studies (Craig, 1963) sedimentary carbonate sources could partially mask the isotopic signature of magmatic CO 2 source active at Yellowstone.…”
Section: Gas Compositionssupporting
confidence: 84%
See 4 more Smart Citations
“…The very negative values of the stable isotopes of water (dD& from À147 to À166 and d 18 O& from À13.5 to À20.7) testify to the main meteoric origin of the water itself, confirming previous investigations (Craig et al, 1956;Bergfeld et al, 2011). Carbon isotopic composition of Yellowstone fumarolic CO 2 , expressed in d 13 C& vs. VPDB notation, varies from À4.2& to À1.7&, suggesting that more than one source may be involved in defining the 13 C. In accordance with previous studies (Craig, 1963) sedimentary carbonate sources could partially mask the isotopic signature of magmatic CO 2 source active at Yellowstone.…”
Section: Gas Compositionssupporting
confidence: 84%
“…1, and the chemical and isotopic compositions are listed in Tables 1 and 2. Replicate samples were collected, analyzed and reported by Bergfeld et al (2011) for many of the species and isotopes reported herein (except for CO, d 15 N). In general, the agreement is excellent.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations